Cascade photoredox/gold catalysis: access to multisubstituted indoles via aminoarylation of alkynes. Issue 100 (28th November 2016) - Qu, Chuanhua; Zhang, Songlin; Du, Hongbin; Zhu, Chengjian
Abstract : A new method for the synthesis of 3-arylindoles has been developed by visible light mediated dual gold/photoredox catalysis. Abstract : A new method for the synthesis of 3-arylindoles has been developed by visible light mediated dual gold/photoredox catalysis. This transformation has many features such as cascade catalysis, high efficiency, redox-neutral reaction conditions and good functional group tolerance. The reaction proceeds through the photoredox-promoted formation of an electrophilic arylgold(iii ) intermediate that undergoes coupling with the arylamine nucleophile.